2022
DOI: 10.1108/ccij-04-2022-0047
|View full text |Cite
|
Sign up to set email alerts
|

Female leadership in communication management in Spain: making a difference in a sexist culture

Abstract: PurposeThis paper aims to explore the position of women in the communication management sector in Spain from their own experiences. The study examines female communication and leadership styles, emphasising the cost of leadership in which they are leaders or led.Design/methodology/approachThis study used a qualitative methodology based on in-depth interviews with 22 women actively working in top companies and agencies: female communication directors, female employees with a female leader and female employees w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
2
0
2
Order By: Relevance
“…It is this ability to energize others that Rosener (2011) refers to when analyzing the participative leadership that tends to be exercised by women. In related areas as Public Relations, it's been found that there are in fact mixed communication and leadership styles, and for example in Spain high levels of self-demand of female communication managers stood out (Zeler et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is this ability to energize others that Rosener (2011) refers to when analyzing the participative leadership that tends to be exercised by women. In related areas as Public Relations, it's been found that there are in fact mixed communication and leadership styles, and for example in Spain high levels of self-demand of female communication managers stood out (Zeler et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Kepemimpinan dalam organisasi merupakan faktor penting dalam menentukan pencapaian tujuan yang telah ditetapkan oleh organisasi (Mus & Sinring, 2021). Kepemimpinan kolektif merupakan proses kepemimpinan kolaboratif yang saling menguntungkan, yang memungkinkan seluruh elemen sebuah institusi turut ambil bagian dalam membangun sebuah kepastian yang mengakomondasi tujuan bersama (Ileana et al, 2022). Kepemimpinan kolektif adalah metode memimpin yang tidak bertumpu pada segelintir orang/tokoh yang menonjol, karena sifat organisasi tidak hanya milik anggotanya saja tapi juga milik seluruh kaum buruh atau golongan yang diperjuangkannya.…”
Section: Gambar 5 Klasifikasi Tema Artikelunclassified
“…Sin embargo, los estudios se han centrado principalmente en el enfoque organizacional, especialmente en la capacidad profesional de las mujeres de relaciones públicas (Aktas, 2020). La mayoría de las investigaciones encontradas (Aktas, 2020;Erzikova & Berger, 2016;Khalil Tolosa et al, 2018;Molleda & Ferguson, 2004;Moreno, Fuentes-Lara, et al, 2021;Moreno, Khalil-Tolosa, et al, 2021;Polić & Holy, 2021;Tench & Topić, 2017;Triantafillidou & Yannas, 2021;Zeler et al, 2022) reflexionan sobre las barreras y los desafíos de las mujeres en el ámbito laboral de las relaciones públicas (brecha salarial, liderazgo, techo de cristal y mentoría).…”
Section: Introductionunclassified